STUDENTS’ PERCEPTION ON USING SOCIAL MEDIA IN ENGLISH LEARNING AT STATE VOCATIONAL HIGH SCHOOL NUMBER 7 PALEMBANG - Tahrun; Yustita, Rika Yeni; Imaduddin, Fadhilatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
As social media became increasingly integrated into daily life, its potential as a learning tool warrants examination. This study explored the perceptions of students regarding the use of social media in learning English at SMK Negeri 7 Palembang. Employing a descriptive quantitative research method, the study involved 100 students of eleventh grade, selected through simple random sampling. Data were collected using structured questionnaires and analyzed using SPSS 24. The results reveal that Instagram (97%), YouTube (80%), and TikTok (71%) are the most frequently utilized platforms for English learning due to their engaging content and accessibility. On the positive side, most students found social media engaging, flexible, and helpful in terms of vocabulary, pronunciation, listening skills, and building confidence. The challenges were grammar learning, motivation to do tasks, anxiety reduction, and time management were areas where social media was less effective. These findings underscored the importance of integrating social media effectively into educational practices to maximize its benefits and address its limitations.